Auf dem Weg in die Moderne Spekulation und Finanzkrisen im 18. Jahrhundert - Schulte Beerbühl, Margrit (De Gruyter, 2023)
So far, scholarship has classified the speculation crises of the eighteenth century as having had no real economic consequences. This study aims to review this theory by looking at seven speculation crises. It concludes that these crises did not just have all of the central characteristics of modern speculation crises but also became global in scope with considerable economic and social consequences.